Infecção latente por Mycobacterium tuberculosis em transplante defígado: experiência do Hospital das Clínicas da UFMG - Isabela Dias Lauar (2014)
Patients undergoing solid organ transplantation are at higher risk for tuberculosis (TB) than general population, with also increased mortality. Most cases of post-transplant TB arise from reactivation of latent Mycobacterium tuberculosis infection (LTBI). In liver transplantation(LT), treatment of LTBI is even more difficult because of hepatotoxicity associated with the drugs used. Brazil presents a particular context, with overlap between TB endemic area and high number of transplants performed. The aim of this study was to evaluate the prevalence ofLTBI, diagnosed by tuberculin skin test (TST), clinical and laboratory factors associated, and the institution of preventive therapy in liver transplant recipients. A retrospective analysis of medical records from patients who underwent liver transplantation between January 2005 andDecember 2012 was performed. There were 429 liver transplant patients eligible for analysis and 49.7% underwent TST pre-transplant. The TST was positive in 16.4% of them, and the presence of previous contact with TB patients and Child A classification, when compared with Child C, were associated with positivity. Treatment of LTBI was prescribed to 34.3% ofthe patients with a positive result, and the preventive therapy was maintained for six months or more in 25% of these patients. In our study we observed a lower prevalence of LTBI, than expected, probably due to limitations of TST for tracking patients with impaired hepatic function. Treatment of LTBI is difficult in these patients with impaired liver function. It is necessary to improve diagnostic methods and treatment of LTBI since TB is a disease with high morbidity and mortality in extremely vulnerable population